An evaluation of the transition from an amateur to professional culture within Hong Kong`s Elite Rugby Programme - Hall, A. J. A.; English, C.; Jones, L.; Westbury, T.; Martindale, R. (Sports Coaching Review, 2024)
Currently little is known about the development of high-performance cultures in emerging nations. This study is the first of its kind examining an emerging rugby nation`s transition from an amateur to a professional full-time fifteen-a-side programme. Eleven full-time professional male rugby union players, the Head of the Hong Kong Rugby Union`s (HKRU) Elite Rugby Programme(ERP) and the HKRU`s peripatetic sport psychologist were interviewed. Inductive thematic analysis of semi-structured interview data revealed four emerging themes, namely; 1) an amateur environment that required change; 2) ERP`s professional culture building blocks; 3) leadership strategy and managing key stake holders and 4) managing on-going challenges in the ERP`s professional culture. Theoretical and applied implications for practitioners and programme leaders responsible for driving cultural change in their respective environments are discussed.